Menumbuhkan Bisnis Digital dengan “Grow with Google” Implementasi Teknologi Era Pandemi Covid-19: Growing Digital Business by “Grow with Google” Implementation of Technology in the Era of Covid-19 Pandemic - Fanny Novika; Fida Fathiyah Addini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Covid-19 pandemic that occurred in Indonesia had an impact on various sectors. The decline in activity and changes to digital systems due to the pandemic are the main factors causing the impact on society. One of the sectors affected is the business sector. Not a few businesses were forced to close because they were unable to deal with changes to the digital system. Google as the largest technology company has a product in the form of training for business people for free. Google also offers the appearance of a business profile in search results or maps. This activity aims to provide literacy and assist business people to improve their competence in using Google products. Literacy is carried out as the initial foundation for business people regarding the basics of digital marketing. Competency improvement is achieved by participating in skills training from Google and applying business profile media, maps search, and advertising media. The results of this activity indicate that the final knowledge of the participants about digital marketing is quite good and there is additional knowledge about business-related products from Google. In addition, one of the selected business owners has been assisted in successfully using business-related products from Google and advertising on Google.